Downregulation of miR203 induces overexpression of PIK3CA and predicts poor prognosis of gastric cancer patients - Liang M; Shi B; Liu J; He L; Yi G; Zhou L; Yu G; Zhou X (Dove Medical Press, 2015)
Min Liang,1,* Boyun Shi,1,* Jifang Liu,1 Lu He,2 Gao Yi,1 Lin Zhou,1 Guifang Yu,1 Xinke Zhou1,* 1Department of Oncology, The fifth affiliated hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Department of radiotherapy, Affiliated Cancer Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China *These authors contributed equally to this work Background: Despite advances in clinical therapies and technologies, the prognosis for patients with gastric cancer is still poor. The aim of this study is to investigate new predictive markers for prognosis of gastric cancer.Methods: In this study, we evaluated the expression pattern of PIK3CA in 107 gastric cancer specimens and their adjacent nontumorous tissues. PIK3CA siRNA was synthesized and transfected into gastric cancer cell lines. Colony formation and MTT assays were employed to analyze the cell proliferation. PIK3CA expression was examined by using immunohistochemical analysis and Western blot assay. Transwell invasion assay was used to detect the invasion capability of the cells. Luciferase activity was examined by using 3'-untranslated region luciferase reporter assays.Results: We observed that PIK3CA was significantly upregulated in gastric cancer tissues. High expression level of PIK3CA was detectable in 48 (44.86%) of the gastric cancer specimens, and correlated with poor prognosis. In addition, our study indicated that miR203 inhibits cell proliferation and invasion via directly targeting and suppressing the PIK3CA expression. MiR203 expression is downregulated in gastric cancer tissues. Moreover, low expression level of miR203 predicted poor prognosis of gastric patients and induced overexpression of PIK3CA. Our further study also reported that overexpression of miR203 inhibited phosphorylation of AKT, while cotransfection of PIK3CA reversed the effect of miR203.Conclusion: Our study suggested a miR203-PIK3CA-AKT signaling pathway in gastric cancer cells. This signaling pathway might play an important role in gastric cancer genesis and development. Keywords: AKT, gastric cancer, miR203, PIK3CA, prognosis